Determinants of the Own-Account Worker's Decision to Hire Employees: A Review - Millán, Ana; Millán, José María; Román, Concepción; van Stel, André (Senate Hall, 2015)
Given the increasing numbers of own-account workers in many European economies, an important question for policy makers is to what extent these own-account workers move on to become employers. Yet, empirical research on job creation by own-account workers hardly exists. This paper reviews a small stream of empirical literature which, by using the European Community Household Panel (ECHP), focuses on the determinants of the own-account worker's decision to hire employees. At the individual level, our review suggests the importance of both human capital and liquidity constraints for the decision of hiring employees. At an aggregated level, we find that own-account workers are less likely to hire employees during recessions. Finally, we also detect the importance of some factors at the environmental and institutional level such as a higher education level of employees and consumers, a higher expenditure on employment incentives and a lower degree of employment protection. The evidence from our review may be useful for governments aiming to create a more enabling micro- and macro-environment for employment growth. Keywords: own-account worker, employer, self-employment, hiring, job creation, Europe
Keywords: own-account worker|employer|self-employment|hiring|job creation|Europe